Penelitian Kualitatif Untuk Penciptaan Karya Seni Rupa Topik Rendah Diri - Graciela, Eleonora Maria; Moerdisuroso, Indro (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2023)
This study aims to explore and prove the existence of the invisible lower self as a concern for the process of self-healing and a means of reflection and expression related to psychological processes in art. This study summarizes the data from the questionnaire results for several participants with the following provisions: Indonesian citizens who have experienced low self-esteem or who have or are currently looking for media or solutions to reduce low self-esteem. Steps From planning to development, simulation, distribution of questionnaires, data processing and analysis, and evaluation, several stages were completed. This study examines the relationship between low self-esteem and the creation of works of art. Descriptive research method with data collection in the form of a questionnaire to describe the actual findings in the field. The creation of works of art can help someone who feels inferior be more appreciated and more expressive in expressing thoughts and feelings, and it can also serve as a therapeutic medium for self-healing. Low self-esteem has opportunities for positive and negative impacts depending on the self-management process of each individual who experiences it. For this reason, the process of reflection and application of mindfulness is needed to achieve better change. The results of the questionnaire show participants' patterns of low self-esteem and show the benefits of art activities as a therapeutic medium for self-recovery.